Three-dimensional tunnel face stability analysis with gate layout by discretization-based kinematic approach - Zhao, Benchao; Chen, Gonglei; Xu, Zhengwei; Liu, Haining; Wang, Hongyu; Xing, Bohui (Frontiers in Built Environment, 2025)
Existing approaches for tunnel face stability analysis usually apply for circular cross-sections and solutions for tunnel face stability evaluation with city gate cross-sections by kinematic approach of limit analysis have not been reported. The present study developed a kinematic approach on tunnel face stability analysis for city gate sections by using spatial discretization technique. The proposed discretization-based kinematic approach applies to shallow tunnel stability analysis with cover depth ratio less than 5 by comparison with finite element limit analysis (FELA). The required support pressure increases with the increase of tunnel width, straight wall height and the central angle of the circular arch.